Hyperuricemia is independently associated with endothelial dysfunction in postmenopausal women but not in premenopausal women. Issue 11 (8th November 2013) - Maruhashi, Tatsuya; Nakashima, Ayumu; Soga, Junko; Fujimura, Noritaka; Idei, Naomi; Mikami, Shinsuke; Iwamoto, Yumiko; Kajikawa, Masato; Matsumoto, Takeshi; Hidaka, Takayuki; Kihara, Yasuki; Chayama, Kazuaki; et al.
Abstract : Objectives: The purpose of this study was to determine the relationships between uric acid, endothelial function and cardiovascular risk factors and to investigate whether menopausal status was associated with the relationship between uric acid and endothelial function in women. Design: Cross-sectional study. Setting: 3 general hospitals in Japan. Participants: 749 Japanese women aged 30–74 years recruited from people who underwent health-screening examinations with agreement for measurement of vascular function. Measures: We measured serum concentrations of uric acid and flow-mediated vasodilation (FMD). Percentage of FMD (peak diameter−baseline diameter/baseline diameter) was used for analysis. Endothelial dysfunction was defined as FMD ≤4.90%, division point for the lowest tertile and the middle tertile of FMD. Menopause women were defined as participants without menstruation for over 1 year or participants with a history of hysterectomy or bilateral oophorectomy. Results: Of the 749 participants, 368 (49.1%) were premenopausal women and 381 (50.9%) were postmenopausal women. Age, body mass index, systolic blood pressure, total cholesterol, triglycerides, glucose, estimated glomerular filtration rate and Framingham risk score were significantly correlated with serum uric acid level. FMD showed a gradual decrease in accordance with the serum uric acid level in the entire study population (<4 mg/dL, 6.85±3.65%; 4 to <5 mg/dL, 6.79±3.60%; 5 to <6 mg/dL, 6.24±3.58%; ≥6 mg/dL, 5.27±3.18%; p=0.01). Multivariate analysis revealed that uric acid was a significantly independent risk factor for endothelial dysfunction in postmenopausal women (OR 1.23, 95% CI 1.01 to 1.50), but not in premenopausal women. Conclusions: These findings suggest that uric acid can be used as a risk marker of endothelial dysfunction in a female population, and particularly as an independent risk factor in postmenopausal women but not in premenopausal women. Registration number of the study: UMIN000003409.